INTELLECTUAL CAPITAL, GOODWILL DAN NILAI PERUSAHAAN: PERAN GOOD CORPORATE GOVERNANCE - Puspita, Kurnia Ayu; Rahman, Taufikur (J-ISCAN: Journal of Islamic Accounting Research, 2025)
This study aims to determine the effect of intellectual capital and goodwill on firm value moderated by good corporate governance in companies listed on the Jakarta Islamic Index 70 for the period 2021-2023. This type of research is an explanatory quantitative method with a population of all companies listed on the JII 70 for the period 2021-2023. The sample of this study was determined using the purposive sampling method to obtain 93 samples. The type of data used is panel data. The hypothesis of this study was tested using the Moderated Regression Analysis (MRA) test with the eviews software analysis tool version 13. The results of this study indicate that the intellectual capital variable has a negative and significant effect on firm value, while goodwill has a positive and significant effect on firm value. This study also shows that good corporate governance is able to moderate the effect of intellectual capital and goodwill on firm value.